Kajian Politik Melalui Kebijakan Pengaturan dalam Ekonomi Islam sebagai Unsur Formil - Ayu, Dena; Arzam, Arzam; Witro, Doli (Al-Amwal : Journal of Islamic Economic Law, 2022)
Political economy is understood as a scientific discipline that discusses political and economic problems and their very complex nature related to thinking about the application of politics and economics. This article uses qualitative research methods. Data collection is done by the library research method. These data are sourced from scientific papers, authoritative books, internet websites, and those related to research topics. The data analysis technique used is a qualitative data engineering model, Miles et al., namely data condensation, data presentation, and drawing conclusions. The study results show that the state's welfare refers to the government's active role in managing the economy. Therefore, the source of state finances is the driving force for the welfare of the state and society. In Indonesia, the government has detailed regulated how state financial resources are obtained and issued for the public benefit. Judging from the history of Islamic economic politics that has been carried out during the time of the Prophet until now, financial sources such as business, taxes, and public debt have become significant contributions to the Indonesian government in running the economy.